Polyunsaturated fatty acid metabolism - Burdge, Graham (Academic Press ; AOCS Press, 2018)
Polyunsaturated Fatty Acid Metabolism explores a number of major roles of PUFA in the body, including its role as a component of cell membranes and how it provides substrates for the synthesis of lipid second messengers. Recent studies are unraveling the effect of interactions between diet and endocrine factors and genetic and epigenetic variation on the regulation of PUFA biosynthesis in animals. Together, these recent findings provide novel insights into the impact of differences in PUFA supply on health. This book captures these findings in a manner that marks the state-of-the-art, placing them in the wider context of PUFA metabolism and nutritional science. Users will find a comprehensive discussion on the topic that presents the contributions of leading researchers who combine their knowledge to create a cohesive academic resource for researchers, those involved in production, and health policymakers.